Seminar TOEFL Upskill Mahasiswa Pendidikan Bahasa Inggris ESCO IAIN Bengkulu - Sembiring, Lina; Rullyanti, Merry; Pradana, Ami; Pungkaswani, Tommi; Sangian, Engga (Universitas Dehasen Bengkulu, 2022)
TOEFL (Test of English as Foreign Language) training is a necessity for students at IAIN Bengkulu, especially for final year students who will take the TOEFL test as one of the requirements for graduation or when entering the world of work. One of them at IAIN Bengkulu who is used as a partner is the IAIN English Club Students. The main problem faced by partners is the lack of understanding regarding TOEFL so that the TOEFL scores of students in the IAIN English Club Student environment are still not in line with the expected targets. Therefore, community service activities carried out by the academic community in the English Literature Study Program need to be carried out as a form of practicing the Tri Dharma of Higher Education. The aim of this activity is to increase TOEFL scores for students in the IAIN environment. The service method used during training activities is by using the lecture method, question and answer, and practice working on TOEFL questions according to the material prepared by the presenter. The results of community service activities show that there is an increase in student TOEFL scores in the IAIN English Club Student environment.